Pengaruh Selisih Kurs Terhadap Return Saham (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016 - 2018) - Ainul Yakin; Abdul Wahid Mahsuni; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study was conducted with the aim of knowing the effect of foreign exchange differences on stock returns of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research is archival research because what will be examined is in the form of written facts (documents) or in the form of archives. And the data source used is secondary data source. The results of the correlation analysis between the Foreign Exchange Profit and Loss variable and the Stock Return variable obtained a correlation coefficient of 0.400 with a probability of 0.000, meaning that the Foreign Exchange Profit and Loss variable and the Stock Return variable have a significant relationship at the 95% confidence level. Meanwhile, the regression coefficient value of 0.000000000004628 is positive, meaning that the effect of foreign exchange differences on stock returns is unidirectional. Thus, it can be concluded that there is a significant positive effect between the exchange rate difference and stock returns, meaning that if the exchange rate difference increases, the stock return also increases. On the other hand, if stock returns increase, the exchange rate difference will also increase.Keywords: Exchange difference, stock return.